Effects of Thermal and Solvent Aging on Breakdown Voltage of TPE, PBT/PET Alloy, and PBT Insulated Low Voltage Electric Wire. (9th July 2013) - Park, Eun-Soo
Abstract : Tests were performed to evaluate the effects of thermal and solvent aging on the mechanical and dielectric breakdown properties of four types of polyester resins, namely, the insulation layer of poly(butylene terephthalat) (PBT)- based thermoplastic elastomer (TPE, TPE1), poly(butylene 2, 6-naphthalate)-based TPE (TPE2), PBT/poly(ethylene terephthalate) alloy (Alloy), and PBT extruded onto a copper conductor of low voltage electric wire. The tensile specimens used in this series were prepared from the same extruded resins. The prepared electric wires and tensile specimens were thermally aged in air and in toluene, xylene, TCB, and NMP. When Alloy and PBT were thermally aged in toluene, xylene and TCB at 120°C for 6 h, the tensile properties were significantly decreased compared to TPE1 and TPE2 at the same condition. The reduction of elongation at break of Alloy was more discernible than that of PBT. This result indicated that Alloy is more affected by thermal and solvent ageing. Among them, TPE2 showed the highest breakdown voltage (BDV), and it has also the highest BDV after thermal and solvent aging.